2013
DOI: 10.2106/jbjs.l.00310
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Action of Induced Membranes in Bone Repair

Abstract: The induced membranes have osteogenesis-improving capabilities. These capabilities, however, appear to decrease over time. We speculate that the optimal time for performing second-stage surgery may be within a month after implantation of foreign material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
163
2
17

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(193 citation statements)
references
References 18 publications
5
163
2
17
Order By: Relevance
“…Este tejido denominado membrana inducida está ricamente vascularizada, y conformada por colágeno Tipo I y células fibroblásticas externamente e internamente semejante a un epitelio sinovial; la membrana secreta factores de crecimiento en alta concentración (21,22). Esta membrana mejora la incorporación del injerto óseo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Este tejido denominado membrana inducida está ricamente vascularizada, y conformada por colágeno Tipo I y células fibroblásticas externamente e internamente semejante a un epitelio sinovial; la membrana secreta factores de crecimiento en alta concentración (21,22). Esta membrana mejora la incorporación del injerto óseo.…”
Section: Discussionunclassified
“…El espaciador induce la formación de la membrana de Masquelet, que es un tejido vascularizado rico en factores de crecimiento como el factor de crecimiento del endotelio vascular (VEGF) y factor de crecimiento transformante beta (TGF-ß1) (21,22). La segunda etapa se realiza entre cuatro a ocho semanas después: se retira el espaciador preservando cuidadosamente la membrana inducida y se sustituye por injerto óseo esponjoso autólogo, La función de la membrana inducida es rodear al injerto óseo y nutrirlo, evitando su reabsorción.…”
Section: Introductionunclassified
“…Although the induced membrane method has been well-studied and reported on in the last 12 years [1,8], the technique has usually been described in adults and primarily employed for posttraumatic defects. Pelissier et al [5] reported that the best timing for the active membrane effectiveness, with highest cytokine concentrations, is 4 weeks to 6 weeks after placement of the antibiotic-cement implant.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…1,2 Masquelet describes induced membranes as an ''in situ growth factor delivery system'' and many subsequent studies have demonstrated the intrinsic bioactivity of membranes grown around PMMA space maintainers. 1,3 Intrinsic membrane factors that can ultimately promote bone growth in the second reconstructive stage include osteogenic and angiogenic growth factors and pro-and anti-inflammatory cytokines. [3][4][5] The presence of these factors has been demonstrated in both human and animal induced membranes over PMMA.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Intrinsic membrane factors that can ultimately promote bone growth in the second reconstructive stage include osteogenic and angiogenic growth factors and pro-and anti-inflammatory cytokines. [3][4][5] The presence of these factors has been demonstrated in both human and animal induced membranes over PMMA. 3,[5][6][7] Ultimately, this membrane serves as an endogenously derived depot of growth factors for the second stage of reconstruction, which involves the removal of the PMMA construct and definitive reconstruction with a graft or flap.…”
Section: Introductionmentioning
confidence: 99%